Isolation and characterization of Leptospira interrogans serovar Copenhageni from a dog from Saint Kitts. (23rd October 2017) - Larson, Christopher R.; Dennis, Michelle; Nair, Rajeev V.; Llanes, Alejandro; Peda, Andrea; Welcome, Shamara; Rajeev, Sreekumari
Abstract : Introduction. Leptospirosis is a zoonotic bacterial disease of global distribution affecting humans and animals. The initial phase of leptospirosis resembles many other febrile illness and due to its broad and biphasic clinical manifestations, selection and implementation of appropriate diagnostic tests can be challenging. Case presentation. This report describes a case investigation of a 14 weeks old male, orphan puppy, presented with generalised jaundice, anemia, weakness, and anorexia. Clinical abnormalities included the evidence of renal and hepatic failure. Antemortem and postmortem diagnostic investigations were conducted to identify the cause of illness. PCR testing and culture of blood was positive for Leptospira sp. Necropsy followed by histopathology evaluation revealed lesions compatible with liver and kidney damage consisting of marked diffuse hepatocellular dissociation, acute renal tubular necrosis, and mild interstitial nephritis. Conclusion. Multiple diagnostic techniques including bacterial isolation confirmed Leptospira infection in this puppy. Whole genome sequencing and analysis identified the Leptospira sp. isolated from this puppy as Leptospira interrogans serovar Copenhageni. To our knowledge, this case report describes the first isolation of Leptospira from Saint Kitts. This case highlights the usefulness of including multiple diagnostic tests for the diagnosis and epidemiological investigation of Leptospira infection. Accurate diagnosis followed by timely intervention can prevent case fatality and mortality in infected patients.